The Magnetism of the Human Rights Act 1998 - Lester, Lord (Victoria University of Wellington Law Review, 2002)
Anthony Lester QC discusses the impact of the UK Human Rights Act 1998 ('UK Act') in the United Kingdom and compares its aspects to the New Zealand Bill of Rights Act 1990. The article begins with an overview of constitutional developments in the United Kingdom, and a brief political background to the UK Act. The author discusses section 3 of the UK Act, which imposes a duty on courts and tribunals to strive to avoid incompatibility between domestic legislation and the European Convention on Human Rights ('Convention'), and section 4, which empowers the Court to make a declaration of incompatibility as a last resort. The article also explores the principle of proportionality, the impact of the UK Act on private law relationships, and section 19 of the UK Act which requires the Minister in charge of Bills to show declare whether a new bill is consistent with the Convention. The author concludes that the UK Act weaves Convention rights into the very fabric of UK common law and legislation, and the judiciary will have a key role in developing the constitutional principles of public law in both the UK and New Zealand